Using Low-immersive Virtual Reality in Online Learning: Field Notes from Environmental Management Education - Rawson, Rebecca; Okere, Uchechukwu; Tooth, Owen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Recent research in the field of virtual reality (VR) education is dominated by the application, experience, and effectiveness of high-immersive environments. However, high-immersive VR may not be accessible to all learners, with online distance learning students in particular unable to fully engage without being supplied with appropriate accessories. These field notes shed light on the role of low-immersive VR as a desktop tool for online distance learning students, exploring student experience of using 360° virtual spaces to undertake a summative assessment. Primary data collection in the form of an anonymous online survey was employed to gather feedback from postgraduate environmental management students who used low-immersive VR to undertake an environmental management system audit of a university campus. Quantitative results were analysed using descriptive statistics and qualitative responses using thematic analysis. Findings indicated that with guidance from the academic teaching staff and practice using the software, the majority of students felt both prepared and happy to undertake a summative assessment using VR spaces. Skills development and an appreciation of the effectiveness of the assessment approach were also highlighted as positive outcomes reinforcing findings from literature on the value of VR to improve learning outcomes particularly with practical tasks. Limitations of the assessment content and software were however noted by students, but both could be resolved with adaptations to the tool. It is hoped this research will be valuable to online education providers to demonstrate the value of using low-immersive VR within their programmes.